Pengaruh Pengawasan, Responsibilitas Kerja Dan Kepercayaan Terhadap Kepuasan Pelanggan Pada PT Rigel Segara Batam - Eny Widyawati; Lalu Muhammad Arif Rahman; Hendri Herman (LPPM Universitas Jambi, 2022)
In testing the hypothesis whether the Supervision variable affects customer satisfaction, then because t calculate (-0.782) < t table (1,677), then Ho is accepted, that is; The regression coefficient is not significant or the supervision variable has no effect on customer satisfaction pt. Rigel Segara Batam. In hypothesis testing whether the Work Responsibilities variable affects Customer Satisfaction, then Because t calculate (11,170) > t table (1,677), then Ho is rejected, that is; Significant regression coefficient or work responsibility variable affects the Customer Satisfaction variable PT. Rigel Segara Batam. In hypothesis testing whether the Trust variable affects Customer Satisfaction, then Because t calculate (-0.218) < t table (1,677), then Ho is accepted, that is; The regression coefficient is not significant or the Trust variable has no effect on the customer satisfaction variable PT. Rigel Segara Batam. In hypothesis testing whether the variables of Supervision, Work Responsibilities and Trust simultaneously affect customer satisfaction. The Anova test produces a calculated F number of 40.676 > F table of 2.81 with a significance level (probability number) of 0.000. F count > F table then Ho is rejected. Then the regression coefficient of Supervision (X1), Work Responsibility (X2) and Trust (X3) simultaneously has a significant effect on the customer satisfaction variable (Y) satisfaction of PT. Rigel Segara Batam